You say USMCA, or T-MEC and I say CUSMA: The New NAFTA – let’s call the whole thing ON - Eugene Beaulieu; Dylan Klemen (The School of Public Policy Publications, 2020)
When U.S. President Donald Trump declared that the North American Free Trade Agreement (NAFTA) was the worst trade agreement ever, and threatened to rip it up, it seemed that the very foundations of the North American economy were about to be shaken up. Nor did it help matters that Trump pulled out of the TransPacific Partnership (TPP), withdrew from the World Trade Organization (WTO) and topped all that off by using aggressive trade tactics against major U.S. trade partners like Canada, Mexico and China. Fortunately, nothing of the sort happened, and the final, revised agreement, recently ratified by Canada, will make incremental rather than earth-shattering changes to free trade flows between Canada, the U.S., and Mexico. Its biggest contribution to the economy is that it puts an end to the uncertainty around the investment climate caused by Trump’s actions. The new NAFTA – referred to in Canada as the Canada-United States-Mexico Agreement (CUSMA) – turned out not to be a game-changer. The old NAFTA, which came into force in 1994, needed updating and its successor improves upon it incrementally. Its economic impact is likely to be a modest one, but its benefits for Western Canada are especially worth noting